Cytauxzoon sp. and Hepatozoon spp. in Domestic Cats: A Preliminary Study in North-Eastern Italy - Marika Grillini (Pathogens, 2021)
Knowledge on the presence of Cytauxzoon sp. and Hepatozoon spp. in Italy is scant and mostly limited to a few areas of Northern and Southern regions, respectively. The present study updated the current epidemiological scenario by investigating the occurrence of these protozoa in domestic cats from three broad regions of North-Eastern Italy. Blood samples from cats at risk of vector-borne diseases were processed by PCR to detect Cytauxzoon and Hepatozoon DNA. Blood smears were observed for haemoparasite inclusions. The influence of cat individual data (e.g., provenance, management, indoor/outdoor lifestyle) on the prevalence of haemoprotozoan infections was statistically evaluated. Among 158 cats, Cytauxzoon and Hepatozoon DNA were detected in 6 (3.8%) and 26 (16.5%) animals, respectively. No Hepatozoon gamonts were detected in blood smears, whereas all Cytauxzoon PCR-positive samples were microscopically positive, though with low levels of parasitaemia. Two species of Hepatozoon were identified, Hepatozoon felis (n = 10) and Hepatozoon silvestris (n = 16). Hepatozoon silvestris prevalence values were significantly (p < 0.05) higher in the region Friuli Venezia Giulia and in stray cats. Cytauxzoon sp. was detected in 6/39 (15.4%) stray cats from Friuli Venezia Giulia (Trieste province). These data add new information on the occurrence of these neglected protozoa in domestic cats’ populations.